2012
DOI: 10.1186/2047-783x-17-5
|View full text |Cite
|
Sign up to set email alerts
|

Literature survey on epidemiology and pathology of cardiac fibroma

Abstract: BackgroundAlthough cardiac fibroma has been regarded as benign tumor, it presents various symptoms and may lead to death. Unfortunately, only a few studies have reported the epidemiology, embryology, and histopathology of the tumor, and the factors predicting poorer outcome are still obscured.MethodsIn July 2011 we searched for English and Japanese cases of cardiac fibroma using the PubMed and IgakuChuoZasshi databases. We then extracted and sampled raw data from the selected publications in accordance with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…It typically presents during childhood and patients have a mean age at operation of 11-18 years. 1,4,6 The knowledge pertaining to surgical management of cardiac fibromas in adults is limited to case reports and reviews of the literature. 7,8 Cardiac fibromas can occur in the atria, interventricular septum, or ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It typically presents during childhood and patients have a mean age at operation of 11-18 years. 1,4,6 The knowledge pertaining to surgical management of cardiac fibromas in adults is limited to case reports and reviews of the literature. 7,8 Cardiac fibromas can occur in the atria, interventricular septum, or ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Cardiac fibromas can occur in the atria, interventricular septum, or ventricle. 6 They most commonly originate in the left ventricle. 7 Our case of a RV fibroma is an uncommon occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac fibromas are regarded as benign tumors, although there are several associated factors predicting poorer outcome, including younger age at diagnosis and septal involvement [17]. Our only patient with a cardiac fibroma was diagnosed at the early age of 13 years owing to extensive tumor growth in the relatively small heart of a teenager.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the location of the tumor in the heart, the presenting symptoms may vary extensively [1,5,6,11,13,17,18]. In our study, all patients (100%) presented with dyspnea on admission, followed by chest pain (43.5%), cough (43.5%), orthopnea (17.4%), sweating (13%), palpitations (8.7%), nausea (8.7%), vomiting (4.3%), fever (4.3%), lymphadenopathy (4.3%) and palpable mass (4.3%).…”
Section: Discussionmentioning
confidence: 99%
“…They show a high possibility of affecting the conduction system, which results in arrhythmia, conduction blocking and ventricular tachycardia that may cause sudden death, which occurs in one-third of the patients [3]. A study has shown that a fibroma located in the septal regions is a significant prognostic factor due to its high tendency for arrhythmias [7]. It may block the outflow or inflow tracts, influencing the hemodynamics, which results in chest pain, shortness of breath or even heart failure.…”
Section: Discussionmentioning
confidence: 99%